(untitled) (Global Journal of Science Frontier Research, 2023)
Wetlands known as Haors in Bangladesh are vital ecosystems that provide essential ecological services and support diverse biodiversity However they face increasing threats due to extensive tourists visits unawareness about environment preservation and unsustainable development practices The Haor Eco-Interpretation Center in Moulvibazar Sylhet Bangladesh emerges as a pioneering initiative to address these challenges by combining environmental education and sustainable design principles This paper provides an overview of the Haor Eco-Interpretation Center s objectives strategies and significance The center serves as a unique model for interpreting the Haor ecosystem while promoting sustainability through its architectural and operational features The key elements of this initiative include visitor education research facilities and eco-sensitive design principles